Biological Reconstruction for Metacarpal Osteofibrous Dysplasia Treatment: A Case Report - Primadika Rubiansyah; Arazy Gifta Prima; Nursanti Apriyani (HM Publisher, 2023)
Background: Osteofibrous dysplasia is a rare benign bone tumor characterized by abnormal differentiation of fibrous tissue in bone and commonly involves the maxilla, mandible, and tibia and affects children less than 10 years old. Osteofibrous dysplasia affecting the metacarpal is a very rare case. This study presents a case report to present biological reconstruction in the management of metacarpal osteofibrous dysplasia. Case presentation: A 48-year-old female presented with swelling and pain in her right hand over 1 year. On examination, palpable mass with immobile and hard consistency on the first metacarpal and distal neurovascular within normal limit. Radiographic examination (X-ray and MRI) supports osteofibrous dysplasia. We performed complete resection of the first metacarpal and used a fibular graft to maintain length, followed by arthroplasty of the first metacarpophalangeal joint and arthrodesis of the first carpometacarpal joint. Pathological results showed a Chinese letter appearance with osteoblastic rimming that confirmed osteofibrous dysplasia. After 6 months of follow-up, there is no recurrence, and the functional outcome is excellent (MSTS score 93,33%). Conclusion: Osteofibrous dysplasia on the metacarpal and affected adult is a very rare case. Treatment with complete resection of the metacarpal, using a fibular graft to maintain bone length, and arthroplasty MCP joint will give good results (MSTS score 93,33%). Follow-up for recurrence is necessary.